Distribution Network Planning Considering Distributed Generation by Genetic Algorithm Combined with Graph Theory - Ouyang, Wu; Cheng, Haozhong; Zhang, Xiubin; Yao, Liangzhong; Bazargan, Masoud (Electric power components and systems, 2010)
Due to requirements for improving energy efficiency and meeting renewable and clean energy targets, an increasing amount of distributed generation is being connected to the distribution network. In order to facilitate increasing levels of distributed generation, the medium-voltage distribution network planning method considering distributed generation connection is proposed in this article. In addition to constraints in the conventional medium-voltage network planning model, constraints related to distributed generation connection, such as short-circuit capacity and short-circuit ratio, are considered in the new planning model. To overcome the problems of low heritability and topological infeasibility of the existing genetic algorithm applied to the distribution network planning, this article develops the efficient genetic algorithm combined with graph theory, which avoids the generation of unfeasible configurations. The efficiency of the proposed planning method is shown using a realistic region distribution network in Shanghai.